Developmental regulators of Kranz anatomy - Sedelnikova, O (2016)
The C4 biochemical pathway is the most efficient form of photosynthesis in warm environments and introducing this system into globally significant, but less efficient, C3 photosynthetic crops could bring major yield increases. The most photosynthetically efficient C4 grass species have a specialised leaf anatomy characterised by high vein density with two distinct cell types radially arranged around the vascular bundles (Kranz anatomy). Although this anatomy was first described in 1882, the genetic regulators controlling Kranz development are still not known. In recent years, transcriptomic analysis has allowed researchers to identify candidate Kranz regulator genes, and a model for Kranz development has been proposed, however, this model has not been experimentally validated. This study used in situ hybridisation to visualise expression patterns for a set of candidate Kranz regulator genes in maize and the orthologous genes in rice. Further, morphological analysis of rice lines with constitutive expression of the candidate Kranz regulator genes AINTEGUMENTA 1 and DAG-LIKE 1 and 2 were used to characterise protein function during C3 monocot leaf development. The function of maize AINTEGUMENTA in the C3 eudicot arabidopsis was also investigated. The results of the in situ hybridisation experiments led to the refinement of the Kranz model and identified potential roles for the candidate regulators during leaf development. The constitutive expression experiments highlighted the regulatory differences between eudicot and monocot leaf development and implicated the regulation of auxin-cytokinin homeostatis as a key factor in Kranz development. Ultimately, this work can be used to guide research into Kranz development and has direct implications for engineering C4 photosynthesis into rice.